Analisis Kepuasan Subkontraktor Terhadap Pelayanan Dan Fasilitas Pengadaan Jasa Divisi Supply Chain PT X - Naomi R. Sidabutar; Hafid Syaifullah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
PT X is a company engaged in producing ships. PT In the research, a validity test was carried out to determine whether the questions given did not produce deviant (valid) data as measured by the Pearson correlation. Then, this research also carried out a reliability test to determine whether the measuring instrument remained consistent if the measurement was carried out twice or more using the Cronbach's Alpha (a) formula. From the research data, valid variables were obtained, including; Friendliness, Good communication, Willingness and readiness, Efforts to establish good relationships, Easy to contact, Cleanliness of the room, The room is not noisy, Quick service, Bright room light, Does not discriminate between subcontractors, Quick approval of offers, Fast issuance of contracts, Comfortable room, and Accuracy Employee. In this research, all variables were found to be valid, so the next step that must be taken is to carry out reliability calculations because the variables in the questionnaire are valid. From the results of reliability calculations, the Cronbach's Alpha value > significance level value is 0.770 > 0.6, so the instrument is said to be reliable. From the research obtained with IBM SPSS software, it is useful for carrying out validity and reliability tests in analyzing the level of subcontractor satisfaction with facilities and services in the Procurement Services Division of PT X's Supply Chain clearly and optimally.